Pengaruh Penggunaan Media Kartu Angka Terhadap Kemampuan Mengenal Lambang Bilangan Pada Anak Kelompok A - Agustina Ernawati; Baik Nilawati Astini; Ika Rachmayani; Fahruddin Fahruddin (Indonesian Publication Center, 2022)
This study aims to determine the effect of the number card game on the ability to recognize number symbols in group A children in Kindergarten, Langgudu District, Bima Regency, in the 2021/2022 academic year. This study uses a quantitative experimental pre-experimental design method with a one-group pretest-posttest design. The sample in this study was group A children in TK Langgudu District, a total of 24 people consisting of 13 boys and 11 girls. Sampling in this study used non-probability sampling with a purposive sampling technique. Data collection techniques in the form of observation and checklist. The analysis technique includes a normality test, hypothesis test and statistical hypothesis. The results of the normality test for the pretest value of 0.097 and the post-test value of 0.160 with a significance value > 0.05 which means that the pretest and post-test data are normally distributed. After the data is normally distributed, it is continued with hypothesis testing using paired sample t-test on the pretest and post-test values ??with sig. 2 tailed is 0.000 <0.05 with a t value of 59.98 > t table 1.711 which means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The value of Ha in question is that there is a difference between the pretest and post-test values ??so it can be concluded that